IoT PCR for pandemic disease detection and its spread monitoring - Zhu, Hanliang; Podesva, Pavel; Liu, Xiaocheng; Zhang, Haoqing; Teply, Tomas; Xu, Ying; Chang, Honglong; Qian, Airong; Lei, Yingfeng; Li, Yu; Niculescu, Andreea; Iliescu, Ciprian; et al. (Sensors and actuators. B, Chemical, 2020)
During infectious disease outbreaks, the centers for disease control need to monitor particular areas. Considerable effort has been invested in the development of portable, user-friendly, and cost-effective systems for point-of-care (POC) diagnostics, which could also create an Internet of Things (IoT) for healthcare via a global network. However, at present IoT based on a functional POC instrument is not available. Here we show a fast, user-friendly, and affordable IoT system based on a miniaturized polymerase chain reaction device. We demonstrated the system's capability by amplification of complementary deoxyribonucleic acid (cDNA) of the dengue fever virus. The resulting data were then automatically uploaded via a Bluetooth interface to an Android-based smartphone and then wirelessly sent to a global network, instantly making the test results available anywhere in the world. The IoT system presented here could become an essential tool for healthcare centers to tackle infectious disease outbreaks identified either by DNA or ribonucleic acid.
Keywords: PCR; Infectious diseases; Dengue fever; IoT